2015
DOI: 10.1080/08897077.2015.1011820
|View full text |Cite
|
Sign up to set email alerts
|

Harm Reduction Agencies as a Potential Site for Buprenorphine Treatment

Abstract: Introduction Harm reduction agencies complement addiction treatment by providing diverse services that improve the health of people who use drugs. Buprenorphine maintenance treatment (BMT) is an effective opioid addiction treatment that may be provided from flexible settings, potentially including harm reduction agencies. This study investigated attitudes toward different potential sites for BMT (harm reduction agencies, general medical clinics, and drug treatment programs) among harm reduction clients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Second, medication assisted therapy (MAT) should be made available to PWID and other opioid users who wish to stop. Buprenorphine or methadone could be offered in UHRN DICs since many people who use drugs around the world have expressed their preference for MAT in harm reduction facilities rather than medical clinics, due in part to the more tolerant and welcoming environments found in these locations [38]. In addition, the UHRN has reported that many people who use drugs avoid medical clinics because they fear being reported to police or otherwise face discrimination from staff [39].…”
Section: Discussionmentioning
confidence: 99%
“…Second, medication assisted therapy (MAT) should be made available to PWID and other opioid users who wish to stop. Buprenorphine or methadone could be offered in UHRN DICs since many people who use drugs around the world have expressed their preference for MAT in harm reduction facilities rather than medical clinics, due in part to the more tolerant and welcoming environments found in these locations [38]. In addition, the UHRN has reported that many people who use drugs avoid medical clinics because they fear being reported to police or otherwise face discrimination from staff [39].…”
Section: Discussionmentioning
confidence: 99%
“…This requirement created multiple barriers for PWUD trying to access MOUD. 37 39 , 40 , 41 , 42 At the onset of the COVID-19 pandemic, the U.S. government waived the Ryan Haight Act’s in-person examination requirement for the initial consultation for buprenorphine treatment, thus permitting the initial consultation to be held via telemedicine for the duration of the COVID-19 emergency. 43 This policy shift allowed SSP leadership to prepare for and implement telemedicine initiatives for buprenorphine treatment in the midst of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, existing harm reduction organizations could offer treatment services, such as MOUD. A recent study of participants drawn from a harm reduction organization found a preference for accessing buprenorphine at the harm reduction organization as opposed to a specialty SUD treatment facility or general medical clinic (Fox et al, 2015). In addition, participants in our study preferred low-barrier treatment centers in which clients are not terminated for using other drugs, especially marijuana.…”
Section: Discussionmentioning
confidence: 99%